Basque separatism vs Catalan independence movement: socio-cultural aspects - M. Kovalchuk (Ибероамериканские тетради, 2019)
The current situation in Spain is characterized by the confrontation of two movements known as «independence movement» and «separatism». Both the Basque region and Catalonia have their own language, culture and a long history of the development of isolation tendencies. However, the objectives and the ways to achieve them have been different for a long time. In order to preserve the sociocultural unity of Spain it is necessary to eliminate the factors that that prevent people from finding the solution to the conflict, and the most important thing is to initiate dialogue, reach a compromise and be ready to stand by the words. It is difficult to imagine that any part will be separated from Spain from the economic point of view and, above all, socio-cultural, because the majority of Spanish population considers Spain as a strong and united State.